Analisis Kesulitan Belajar Siswa Aspek Motivasi Belajar dan Kondisi Kesehatan Fisik Pada Pembelajaran Daring Mata Pelajaran Biologi Kelas XI SMA Negeri 06 Makassar - Murti, Andi Hastialihaesar Dwi; Arsal, Andi Faridah; Muis, Abd (Biology Teaching and Learning, 2021)
Abstract. This study aims to determine the learning difficulties experienced by students in online learning and the efforts made in overcoming students' learning difficulties in biology during the online learning period. The research method used in this study is a qualitative research method. The population in this study were students of class XI SMA Negeri 06 Makassar which consisted of 6 classes, namely XI MIPA 1, XI MIPA 2, XI MIPA 3, XI MIPA 4, XI MIPA 5, and XI MIPA 6. The instrument used was a Likert scale closed questionnaire. The research data were obtained by distributing questionnaires regarding internal factors of student learning difficulties and conducting interviews with biology teachers in class XI of SMAN 06 Makassar. Based on the research results, there are two aspects that have an influence on learning difficulties on students 'internal factors, namely aspects of learning motivation and aspects of students' physical health conditions. In general, efforts to overcome student learning difficulties are based on the diata aspect, namely, by providing excessive motivation to students, both from teachers and from families. Because, the amount of learning motivation received by students will affect the learning outcomes received. In addition, efforts to prevent learning difficulties caused by physical health factors are by taking a moment to rest after using electronic devices for a long time. As well as the need for self-awareness of the importance of maintaining physical health.Keywords: online learning, student learning difficulties, learning motivation, physical health condition